The effects of vitamin A supplementation on some parameters of iron metabolism in a rural population (preschoolers) in Cavite - Lorovico, Minerva B
Subjects included in this study were children aged 3 to 6 years old residing in the rural area of Indang, Cavite. Their diets were supplemented with margarine fortified with Vitamin A. Nutritional status of Vitamin A, iron and protein nutriture were determined and compared before and after the Vitamin A supplementation. After the 8 months supplementation with Vitamin A, serum retinol, serum hemoglobin and serum iron levels of the children were determined and found to have increased significantly. On the other hand, the serum apotransferrin level decreased after the 8 months supplementation. These changes showed that Vitamin A supplementation affected iron metabolism. The interaction may involve mechanism affecting the synthesis of apotransferrin in the following manner: (a) the competitive binding of the transport protein, transthyretin or prealbumin, for transport of retinol and thyroxine could have an effect on the synthesis of apotransferrin; (b) the hormonal behavior of retinoic acid in the nucleus competes with the same promoter region of the hormone thyroxine for the expression of genes; and (c), the important role of Vitamin A in glycosylation of apotransferrin at the post-translational level. No changes were observed in the level of total serum protein, total serum globulin and serum albumin following Vitamin A supplementation. This study has shown the beneficial effect of Vitamin A on iron metabolism and provided useful information on the possible mechanisms on how Vitamin A improves iron mobilization.